Following high-risk newborn babies in a public health unit of Maringá-PR - Lopes, Mislaine Casagrande de Lima; Santander, Claudia Aparecida; Marcon, Sonia Silva (Rev Rene, 2010)
This is a descriptive exploratory study that aimed at characterizing high-risk newborn babies (NB) from a Public Health Unit, and to verify if and how these children have been followed by the health family strategy. Data were collected in June 2007, from medical records of the high-risk newborn. Data revealed that the main risk factors were prematurity, low birth weight and the low maternal age. Most of the children did not receive a monthly check-up as indicated. It was noticed a small number of information regarding family antecedents, vaccines, gestation, childbirth and the child’s nursing history. It was considered that the existence of risk factors among mothers over 17 years of age may be associated to pre and perinatal problems. It was concluded that there is need for an active search on the babies that are not included, as well as awareness regarding the importance of having the complete information on medical records.